PERBANDINGAN KUAT TEKAN BETON MENGGUNAKAN AGREGAT HALUS PASIR SILIKA MALIMPUNG DAN PASIR SUNGAI SADDANG KABUPATEN PINRANG - Fadly, Imam; Hamka, Hamka; Jabir M., Muh.; Fatmawati, Fatmawati (Universitas PGRI Semarang, 2025)
Silica contains impurities that are carried during the sedimentation process. Silica is usually obtained through a mining process that starts from mining quartz sand as a raw material. This study aims to determine the effect of fine aggregate of Malimpung silica sand on the compressive strength of concrete. And to determine the effect of fine aggregate of Saddang river sand on the compressive strength of concrete. In this study, tests were conducted on two types of fine aggregates to determine their effect on the compressive strength of concrete. The research method used is a quantitative experimental method with compressive strength testing at the ages of 7, 14, and 28 days. The results of the study obtained showed that concrete using Malimpung silica sand had a higher compressive strength compared to concrete using Saddang river sand. At the age of 28 days, the compressive strength of concrete with a composition of 100% silica sand reached 28.120 MPa, while concrete with 100% river sand only reached 19.439 MPa.